2001
DOI: 10.1093/humrep/16.10.2211
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and the expression of Bax and Bcl-2 in hyperplasia and adenocarcinoma of the uterine endometrium

Abstract: These results suggest that cells in hyperplasia expressing Bcl-2 might have prolonged survival ability. Neoplastic cells in adenocarcinoma might show apoptosis in association with a decreased expression of Bcl-2 and an increased expression of Bax. Therefore, the frequency of apoptosis and the expression of Bcl-2 and Bax might be correlated with carcinogenesis in the uterine endometrium of humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
2
24
1
1
Order By: Relevance
“…Goumenou et al [12] reported similar bax expression in adenomyotic and endometriotic samples, and no variation according to the phase of the menstrual cycle. Furthermore, previous studies have shown no difference in endometrial bax expression between women with and without endometriosis [27] or between eutopic and ectopic endometrium [26], whereas bax expression was higher in endometrioid carcinomas than in normal and hyperplastic endometrium [22]. We found no correlation between p53 and bax expression.…”
Section: Discussioncontrasting
confidence: 77%
“…Goumenou et al [12] reported similar bax expression in adenomyotic and endometriotic samples, and no variation according to the phase of the menstrual cycle. Furthermore, previous studies have shown no difference in endometrial bax expression between women with and without endometriosis [27] or between eutopic and ectopic endometrium [26], whereas bax expression was higher in endometrioid carcinomas than in normal and hyperplastic endometrium [22]. We found no correlation between p53 and bax expression.…”
Section: Discussioncontrasting
confidence: 77%
“…In the present study, positive correlations were found between WWOX and the antiapoptotic BCL2 gene as well as between WWOX and the BCL2/BAX ratio. Findings of a previous study demonstrated the increasing expression of the proapoptotic BAX gene and decreasing expression of the antiapoptotic BCL2 gene during progression from endometrial hyperplasia to cancer (27). Geisler et al (28) demonstrated that a higher expression level of the Bcl2 protein correlates with favorable clinicopathological variables such as well-differentiated tumor cells, reduced FIGO stage, lack of invasion into lymph node and superficial myometrial invasion (28,29).…”
Section: Discussionmentioning
confidence: 98%
“…Aberrant apoptosis was present in dysfunctional uterine bleeding (Stewart et al 1999) and increasing cellular apoptosis was observed upon progression from endometrial hyperplasia through atypia to adenocarcinoma (Ioffe et al 1998). Moreover, undifferentiated and poorly differentiated endometrial carcinomas paradoxically exhibited higher apoptotic indices when compared with well-differentiated tumors; these high indices correlated inversely with prognosis (Heatley 1995, Kokawa et al 2001b). The highest rates of apoptosis were observed in the rare but aggressive papillary serous and clear cell endometrial carcinomas, characterized by late-stage presentation, extra-uterine invasion, and poor prognosis (Kokawa et al 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…However, aberrant expression of Bcl-2 proteins in endometrial cancers is associated with increased malignancy and poor prognosis (Ioffe et al 1998, Ouyang et al 1998, Sakuragi et al 2002. Decreased levels of the anti-apoptotic Bcl-2 and upregulation of its pro-apoptotic partner Bax, correlate with increased apoptosis and progression from hyperplasia to malignancy in the endometrium (Chieng et al 1996, Henderson et al 1996, Kuwashima et al 1996, Saegusa et al 1996, Mozzetti et al 2000, Kokawa et al 2001b, Peiro et al 2001, Sakuragi et al 2002. PKCa has been shown to phosphorylate Bcl-2, which may be required for optimal anti-apoptotic function (Ruvolo et al 1998, Deng et al 2001.…”
Section: Discussionmentioning
confidence: 99%